Jejunal Duplication Cyst - a Rare Cause of Massive Gastrointestinal Bleeding: A Case Report - Biswas, Rana Kumar; Biswas, Subir Ananda; Md Benzamin, -; Mazumder, Md Wahiduzzaman; Karim, ASM Bazlul (Dhaka Shishu (Children) Hospital Journal, 2021)
Abstract not available DS (Child) H J 2018; 34(1) : 55-58